2018
DOI: 10.1016/j.antiviral.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The molecular tweezer CLR01 inhibits Ebola and Zika virus infection

Abstract: Ebola (EBOV) and Zika viruses (ZIKV) are responsible for recent global health threats. As no preventive vaccines or antiviral drugs against these two re-emerging pathogens are available, we evaluated whether the molecular tweezer CLR01 may inhibit EBOV and ZIKV infection. This small molecule has previously been shown to inactivate HIV-1 and herpes viruses through a selective interaction with lipid-raft-rich regions in the viral envelope, which results in membrane disruption and loss of infectivity. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 53 publications
5
45
1
Order By: Relevance
“…Inspired by the well-established Zika virus infection assay that quantifies the viral envelope (E) protein by a horseradish peroxidase (HRP) coupled antibody ( Aubry et al, 2016 ; Conzelmann et al, 2019 ; Müller et al, 2018 , 2017 ; Röcker et al, 2018 ) we here aimed to detect the spike (S) protein of SARS-CoV-2 by a similar approach. To adapt this in-cell ELISA to measure SARS-CoV-2 infection, we made use of the anti-SARS-CoV/SARS-CoV-2 antibody 1A9 that targets the highly conserved loop region between the HR1 and HR2 in the S2 subunit of the S protein ( Ng et al, 2014 ; Walls et al, 2020 ) ( www.nextstrain.org ( Hadfield et al, 2018 )) and has been verified to bind to SARS-CoV-2 S protein ( Zheng et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the well-established Zika virus infection assay that quantifies the viral envelope (E) protein by a horseradish peroxidase (HRP) coupled antibody ( Aubry et al, 2016 ; Conzelmann et al, 2019 ; Müller et al, 2018 , 2017 ; Röcker et al, 2018 ) we here aimed to detect the spike (S) protein of SARS-CoV-2 by a similar approach. To adapt this in-cell ELISA to measure SARS-CoV-2 infection, we made use of the anti-SARS-CoV/SARS-CoV-2 antibody 1A9 that targets the highly conserved loop region between the HR1 and HR2 in the S2 subunit of the S protein ( Ng et al, 2014 ; Walls et al, 2020 ) ( www.nextstrain.org ( Hadfield et al, 2018 )) and has been verified to bind to SARS-CoV-2 S protein ( Zheng et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cholesterol dependence of DENV entry and post-entry steps have been observed in several mammalian cell lines (Lee et al, 2008 ; Soto-Acosta et al, 2013 ; Martínez-Gutierrez et al, 2014 ), it does not seem to be a general event, because it has been described that cholesterol is not required for Vero (green monkey epithelial kidney cell line) (Acosta et al, 2009 ; Carro and Damonte, 2013 ), HepG2 (Hepatocarcinoma cell line) and ECV304 cells entry (human endothelial cell line) (Rothwell et al, 2009 ). In addition, it has been described that the molecular tweezer CLR01, a small molecule that previously has been shown to inactivate some viruses through a selective interaction with the host-membrane-derived lipid bilayer of the viral envelope, inhibit EBOV (ebola virus) and ZIKV infection (Röcker et al, 2018 ).…”
Section: The Role Of Host Cholesterol During the Flavivirus Life Cyclmentioning
confidence: 99%
“… 15 , 17 , 22 , 23 Unexpectedly, we previously found that CLR01 not only antagonizes the infectivity-enhancing activity of seminal amyloids but also exerts a direct antiviral activity against several enveloped viruses such as HIV-1, hepatitis c virus (HCV), herpes simplex virus type 2 (HSV-2), human cytomegalovirus (HCMV), Zika virus (ZIKV), and Ebola virus. 14 , 24 The antiviral activity is a consequence of the direct interaction of CLR01 with the membrane of the enveloped viral particle, which ultimately results in the loss of virion integrity and hence infectivity. 14 , 24 However, the precise antiviral mechanism of CLR01 remains unclear.…”
Section: Introductionmentioning
confidence: 99%